Hollywood war films, 1937-1945 : an exhaustive filmography of American feature-length motion pictures relating to World War II - Shull, Michael S., 1949- (McFarland & Co., 1996)
""Comprehensive ... recommended ... definitive""--Library Journal; ""no other book comes close ... recommended""--Choice. Part one focuses on movies that reflected America's increasing uneasiness. Part two reveals that many movies made from 1942 through 1945 included at least some allusion to World War II